Case Study in Iranian Criminal system - Zarrokh, Ehsan
Criminal code is so important than other legal code, because its relevance to people life, honor and property. so I think if you want scrutiny develop of society you must note to its criminal law & penal procedure. In Iran we see that all of codes are based on FIGH (Islamic Rules); so it's necessary for Non-Muslim to understand SHARI'A rules, sake realizes roots of Islamic law, Punishments in criminal law are the most important ingredient of SHARI'A rules. In this paper I'm trying to pore over punishments and their reasons that state in Islamic legal books, because one of the basic sources in Islamic law is theories of Islamic jurisconsult that explain in their books and treatises.punishment, Islamic rules, Iranian penal code, Islamic jurisconsult theories. †